CRM adoption and its impact on organisational performance - Law, Ka Yee (2009)
Customer Relationship Management (CRM) which aims at enabling organisations to realize a customer focus is believed to be useful and has risen to the agenda of many organisational strategies. It can be seen as an approach to marketing that has its origins in Relationship Marketing (RM). In Hong Kong, CRM has been gathering attention from attorneys, accountants, merchants, bankers and financial advisors. However, there are few studies specifically investigating the factors that may influence the adoption of CRM. In order to bridge the gap in understanding, an exploratory study utilising in-depth interviews was conducted. A conceptual model was developed in order to deal with the two major objectives in this research 1) to investigate the factors which lead organisations to adopt CRM; and 2) the impact of CRM on the organisational performance. The conceptual model was tested with the relevant hypotheses, using a survey method by mailing questionnaires to the organisations of services industry in Hong Kong. Important findings from the examination of research objectives were discussed with regard to their implications for researchers and practitioners. Analysis results supported that attributes of innovation proposed by Rogers’ (1995), attitude towards change, market orientation, innovation orientation, perceived accessibility of IT solutions, competition intensity and desire of customer intimacy were the antecedents of CRM adoption. Also, it was discovered that information utilisation would be a possible mediator between CRM adoption and the performance. Finally, customer satisfaction, employee satisfaction and business performance was found to be influenced by CRM adoption. Limitations of study were reported together with recommendations for future research programmes.